Ginkgo biloba extract reduces naphthalene-induced oxidative damage in mice - BECEREN, AYFER; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (JOHN WILEY & SONS LTD, 2007)
This investigation elucidated the role of free radicals in naphthalene-induced toxicity and protection by Ginkgo biloba extract (EGb). BALB-c mice of either sex were administered with naphthalene (100 mg/kg; i.p.) for 30 days, along with either saline or EGb (150 mg/kg, orally). At the end of the experiment, following decapitation, lung, liver and kidney tissue samples were taken for histological examination or determination of malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO) activity and collagen contents. In addition, proinflammatory cytokines (TNF-alpha and IL-beta) and total antioxidant capacity (AOC) were assayed in the plasma, while lactate dehydrogenase (LDH) activity was assayed in serum samples. The results revealed that naphthalene caused a significant decrease in GSH level, and significant increases in MDA level, MPO activity and collagen content of tissues. Similarly, plasma cytokines, as well as serum LDH activity, were elevated while AOC was decreased in the naphthalene group compared with the control group. On the other hand, EGb treatment reversed all these biochemical indices. The results demonstrate that EGb extract, by balancing the oxidant-antioxidant status and inhibiting the generation of proinflammatory cytokines and neutrophil infiltration, protects against naphthalene-induced oxidative organ injury. Copyright (c) 2006 John Wiley & Sons, Ltd.
Keywords: naphthalene toxicity; Ginkgo biloba; cytokine; lipid peroxidation; glutathione; myeloperoxidase; EGB 761; INDUCED TOXICITY; NITRIC-OXIDE; STRESS; RATS; MYELOPEROXIDASE; INJURY; CELLS